Reduced subjective response to acute ethanol administration among young men with a broad bipolar phenotype. - Yip, S; Doherty, J; Wakeley, J; Saunders, K; Tzagarakis, C; de Wit, H; Goodwin, G; Rogers, R (2012)
Elevated lifetime prevalence rates of alcohol use disorders (AUDs) are a feature of bipolar disorder (BD). Individuals at-risk for AUDs exhibit blunted subjective responses to alcohol (low levels of response), which may represent a biomarker for AUDs. Thus, individuals at-risk for BD may exhibit low responses to alcohol. Participants were 20 unmedicated adult males who reported high rates of hypomanic experiences (bipolar phenotype participants; BPPs), aged 18 to 21 years, and 20 healthy controls matched on age, gender, IQ, BMI, and weekly alcohol intake. Subjective and pharmacokinetic responses to acute alcohol (0.8 g/kg) vs placebo administration were collected in a randomized, double-blind, cross-over, placebo-controlled, within-subjects design. BPP participants reported significantly lower subjective intoxication effects ('feel high': F=14.2, p=0.001; 'feel effects': F=8.1, p=0.008) across time, but did not differ in their pharmacokinetic, stimulant, or sedative responses. Paradoxically, however, the BPP participants reported significantly higher expectations of the positive effects of alcohol than controls. Our results suggest that unmedicated young males with previous hypomanic experiences exhibit diminished subjective responses to alcohol. These blunted alcohol responses are not attributable to differences in weekly alcohol intake, pharmacokinetic effects (eg, absorption rates), or familial risk of AUDs. These observations suggest that the dampened intoxication may contribute to the increased rates of alcohol misuse in young people at-risk for BD, and suggest possible shared etiological factors in the development of AUDs and BD.